Equity research: GlaxoSmithKline overview and valuation - Ji, Xinglei (2021)
With increase of health and wellness awareness, we feel interested to do an equity research on a pharmaceutical/healthcare company. Since the economy is damaged by Covid-19 pandemic, the big pharmaceuticals firms are developing vaccines for this virus. Therefore, we found GSK, the second largest vaccines firm in the world as our target company. Our consolidated report is divided into 7 parts: Executive Summary, Overview, Investment and Strategic, Past Analysis, Macroeconomics Environment, Forecast and Valuation. In this report, it will cover the following 3 parts: Company and Industry overview, past analysis of GSK’s financial statement and valuation which includes several scenarios to approximate the actual share price of the firm.